PERAN PENYULUH AGAMA DALAM MENGATASI KEKERASAN DALAM RUMAH TANGGA DI KUA SERIRIT KABUPATEN BULELENG - M. Syakur; Amelia Hidayah (Fakultas Dakwah Universitas Ibrahimy, 2026)
A family is a small social unit within the community, living together in a single household led by a head of the family, and bound by blood ties resulting from marriage or other connections. Family life encompasses both joys and sorrows. Families experiencing distress or domestic violence require a place to turn for support and refuge. This study aims to describe the role of religious counselors in addressing domestic violence at the Office of Religious Affairs (KUA) in Seririt District, Buleleng Regency. The study employs a qualitative research method using a case study approach. Data collection techniques included observation, interviews, and documentation, while data analysis involved data reduction, data presentation, and drawing conclusions. The research findings indicate that: (1) the counselor acts as a facilitator by providing guidance to the community to help prevent divorce; and (2) the counselor acts as a motivator by offering guidance and advice—particularly to prospective couples to ensure they are adequately prepared for married life.